2010
DOI: 10.4317/medoral.15.e611
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic and tomographic implant studies: Role in the diagnosis of sinus disorders

Abstract: Objective: To study the presence of sinus disorders and their diagnosis based on clinical and radiographic findings, correlating their presence with tomography tests and panoramic radiography. Study design: We conducted a retrospective study on 152 patients who were seeking implant treatment, thereby allowing us to evaluate 42 patients who had abnormal sinuses. The patients underwent an evaluation of their medical history as well a clinical examination, panoramic radiography and tomographic study. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Other authors emphasize that depending on the degree of sinus pneumatization, the roots can be projected into it, even some of the tips can become coated by the sinus mucosa. In other studies using CT, similar results were obtained regarding the distance between the roots and the sinus, and it was found that a small percentage of patients had roots that extended into the walls of the sinus (8). It has been demonstrated that, in cases of apical periodontitis, when the tip of the tooth root was in contact with the floor of the maxillary sinus, the incidence of mucosal thickening was lower than when the tip of the root exceeded the floor of the maxillary sinus, so the closer the tooth apex is to the floor of the maxillary sinus, the greater the impact on antral tissue (3).…”
Section: Etiology Of Maxillary Sinusitissupporting
confidence: 67%
See 1 more Smart Citation
“…Other authors emphasize that depending on the degree of sinus pneumatization, the roots can be projected into it, even some of the tips can become coated by the sinus mucosa. In other studies using CT, similar results were obtained regarding the distance between the roots and the sinus, and it was found that a small percentage of patients had roots that extended into the walls of the sinus (8). It has been demonstrated that, in cases of apical periodontitis, when the tip of the tooth root was in contact with the floor of the maxillary sinus, the incidence of mucosal thickening was lower than when the tip of the root exceeded the floor of the maxillary sinus, so the closer the tooth apex is to the floor of the maxillary sinus, the greater the impact on antral tissue (3).…”
Section: Etiology Of Maxillary Sinusitissupporting
confidence: 67%
“…On the other hand, recent prospective comparative studies showed no correlation of sinonasal symptoms with MMC (18). Symptomatic cases may occur when the sinus is completely full, the most common clinical manifestations being that of headaches, periorbital and hemifacial pains, and sometimes dizziness, nasal obstruction and recurrent sinusitis, among others (8).…”
Section: Mucous Retention Cystmentioning
confidence: 99%
“…Lower nasal concha and nasal cavities extend and protrude over the maxillary sinus when the patient is positioned too far from the X-ray machine or with the head raised, which produces images that suggest changes in the maxillary sinuses (24). A previous study compared CT with panoramic radiography and concluded that CT remains the most effective test for the diagnosis of inflammatory changes of the maxillary sinuses (16). …”
Section: Discussionmentioning
confidence: 99%
“…Martínez-González et al (16) compared panoramic radiography and CT to evaluate 84 maxillary sinuses and found that panoramic radiography had limitations in the diagnosis of changes in maxillary sinus, whereas CT seemed to be a better imaging tool. Despite the advantages of CT, it is no longer used in routine dental care because of its high radiation doses and cost (16-18). …”
Section: Introductionmentioning
confidence: 99%
“…The roof of the MS and minor changes in the superolateral regions cannot be viewed in detail using panoramic radiography. 21 A different study comparing CBCT with 2D panoramic images has indicated that CBCT remains the most effective radiological method for the evaluation of inflammatory changes in the MS. 22 A CBCT examination of the maxilla is mostly performed prior to a surgical sinus lift and augmentation process for dental implant placement in the maxillary posterior area.…”
Section: Discussionmentioning
confidence: 99%